Analisis Terhadap Gaya Belajar Siswa Sekolah Menengah Di Bandung - Louise M Saija (LPPM Universitas Advent Indonesia, 2020)
Learning style is a behavior that is intentionally done by students in the form of cognitive, affective and psychological behavior to obtain changes in learning. Information about student learning styles can help teachers determine the learning strategies to be used. This study aims to determine how the learning styles of high school students in Bandung. This is descriptive research, and the sample in this study was 275 students from several secondary schools in Bandung. The learning style measurement instrument used is the